Redefining health communication through narrative intersection: opening closed narratives and co-creating meaning - Okuhara, Tsuyoshi; Okada, Hiroko; Yokota, Rie; Kagawa, Yumi (Frontiers in Communication, 2025)
We aimed to propose a new conceptualization of health communication that mitigates the limitations of traditional one-way models by introducing a relational, narrative-based approach that emphasizes mutual understanding. This paper critiques existing definitions and proposes an alternative framework by reviewing interdisciplinary literature on Narrative Medicine, narrative identity theory, and health communication research. The paper introduces “narrative intersection” as a concept that describes how divergent narratives engage in dialogic meaning-making. Health communication is redefined as the study and practice of opening closed narratives and co-creating shared meanings through narrative intersections to improve health. This redefinition shifts focus from merely delivering information to fostering dialog and co-constructing meaning. It provides a unifying framework for diverse domains, such as clinical communication and public health messaging, while addressing issues such as resistance to evidence-based recommendations and the spread of misinformation. Narrative intersections offer a grounded, ethically responsive, and practically relevant framework for advancing health communication by emphasizing the importance of dialog, narrative contexts, and the structural conditions that shape the voices that are heard.